The future of the sugarcane industry in Fiji: climatic, non-climatic stressors, and opportunities for transformation - Medina Hidalgo, Daniela; Mallette, Angela; Nadir, Suhayl; Kumar, Salesh (Frontiers in Sustainable Food Systems, 2024)
This study explores the complex dynamics of Fiji’s sugarcane industry, shedding light on the challenges it faces and the implications for agricultural system resilience and sustainability. The primary aim of the study was to investigate the relationship between climatic and non-climatic stressors and farmers’ decisions to abandon sugarcane farming. A total of 900 farmers were surveyed, which corresponds to approximately 7.5% of the sugarcane farming population in the country. Farmers were sampled using a stratified disproportional random sampling technique, by surveying 300 farmers from each of the three primary sugarcane mill regions in Fiji (Labasa, Lautoka, and Rarawai). Results depict an aging farming population with small land holdings, and limited income and agricultural diversification. While only 4% of farmers are currently considering abandoning sugarcane farming, a further 17.9% are uncertain about their future in the industry. The majority of farmers have been impacted by climate hazards, primarily tropical cyclones and floods, but the degree to which these hazards have affected livelihoods has had an effect on farmers’ willingness to remain in the industry and on the extent to which they implement reactive or anticipatory responses to hazards. The study highlights the need for coordinated efforts to support sustainable intensification and planned adaptation, especially in the face of climate-induced vulnerabilities, this should be a priority as the sector continues to navigate sustainability issues. Additionally, it underscores the importance of transforming the industry to address both climatic and non-climatic stressors. Ultimately, this research offers valuable insights into the multifaceted issues confronting Fiji’s sugarcane sector, and the broader agricultural systems it represents.